Synthesis, self-assembly, and immunological activity of α-galactose-functionalized dendron–lipid amphiphiles. Issue 40 (5th October 2016) - Trant, John F.; Jain, Namrata; Mazzuca, Delfina M.; McIntosh, James T.; Fan, Bo; Haeryfar, S. M. Mansour; Lecommandoux, Sebastien; Gillies, Elizabeth R.
Abstract : A library of α-galactose-functionalized dendron–lipid hybrids were synthesized and the generation dependence of the self-assembly and bioactivity were studied. Abstract : Nanoassemblies presenting multivalent displays of biologically active carbohydrates are of significant interest for a wide array of biomedical applications ranging from drug delivery to immunotherapy. In this study, glycodendron–lipid hybrids were developed as a new and tunable class of dendritic amphiphiles. A modular synthesis was used to prepare dendron–lipid hybrids comprising distearylglycerol and 0 through 4th generation polyester dendrons with peripheral protected amines. Following deprotection of the amines, an isothiocyanate derivative of C -linked α-galactose (α-Gal) was conjugated to the dendron peripheries, affording amphiphiles with 1 to 16 α-Gal moieties. Self-assembly in water through a solvent exchange process resulted in vesicles for the 0 through 2 nd generation systems and micelles for the 3 rd and 4 th generation systems. The critical aggregation concentrations decreased with increasing dendron generation, suggesting that the effects of increasing molar mass dominated over the effects of increasing the hydrophilic weight fraction. The binding of the assemblies to Griffonia simplicifolia Lectin I (GSL 1), a protein with specificity for α-Gal was studied by quantifying the binding of fluorescently labeled assemblies to GSL 1-coated beads. It was found that binding was enhanced for amphiphiles containing higher generation dendrons. Despite their substantial structural differences with the natural ligands for the CD1d receptor, the glycodendron–lipid hybrids were capable of stimulating invariant natural killer T ( i NKT) cells, a class of innate-like T cells that recognize lipid and glycolipid antigens presented by CD1d and that are implicated in a wide range of diseases and conditions including but not limited to infectious diseases, diabetes and cancer.